Sirtuin 7 super-enhancer drives epigenomic reprogramming in hepatocarcinogenesis. (28th January 2022) - Wu, Feng; Xu, Liangliang; Tu, Yalin; Cheung, Otto KW.; Szeto, Lemuel LM.; Mok, Myth TS.; Yang, Weiqin; Kang, Wei; Cao, Qin; Lai, Paul BS.; Chan, Stephen L.; Tan, Patrick; et al.
Abstract: Hepatocellular carcinoma (HCC) is a major cancer burden worldwide with increasing incidence in many developed countries. Super-enhancers (SEs) drive gene expressions required for cell type-specificity and tumor cell identity. However, their roles in HCC remain unclear because of data scarcity from primary tumors. Herein, chromatin profiling of non-alcoholic fatty liver disease (NAFLD)-associated HCCs and matched liver tissues uncovered an average of ∼500 somatically-acquired SEs per patient. The identified SE-target genes were functionally enriched for aberrant metabolism and cancer phenotypes, especially chromatin regulators including deacetylases and Polycomb repressive complexes. Notably, all examined tumors exhibited SE activation of Sirtuin 7 ( SIRT7 ), genome-wide promoter H3K18 deacetylation and concurrent H3K27me3, as well as tumor-suppressor gene silencing. Depletion of SIRT7 SE in hepatoma cells induced global H3K18 acetylation and reactivated key metabolic and immune regulators, leading to marked suppression of tumorigenicity in vitro and in vivo . In concordance, SIRT7 physically interacted with the methyltransferase EZH2, and they were co-expressed in primary HCCs. In summary, our integrative analysis establishes a compendium of SEs in NAFLD-associated HCCs and uncovers SIRT7-driven chromatin regulatory network as potential druggable vulnerability of this increasingly prevalent cancer. Highlights: Analysis of 60 chromatin profiles reveals druggable vulnerability of primary HCCs. Target genes of somatically-acquired SEs are enriched in chromatin regulators. SE-activated SIRT7 drives metabolic and immune dysfunction via chromatin remodeling. SIRT7 physically interacts with EZH2 for cooperative epigenetic silencing.